Qur’anic Wealth Management (At-Tamwil) and Digital Waqf Transformation in Indonesia: A Systematic Literature Review - Khaidir, Widya; Muyasaroh, Nurul; Nasution, Muhammad Irwan Padli; Siregar, Muhammad Habibi (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: As Islamic financial technology (fintech) continues to expand rapidly, the digitalization of waqf presents a strategic opportunity that is both timely and urgent. However, much of the existing scholarship has concentrated narrowly on jurisprudential rulings and technical feasibility, leaving the deeper normative foundations of the Qur’an as a source of Islamic wealth stewardship largely unexplored. Method: This study aims to examine the Qur’anic concept of wealth management (at-tamwīl) through thematic exegesis (maudhū’ī tafsir), and to develop a framework that integrates these principles with digital waqf innovation in Indonesia. A qualitative descriptive design was employed, combining thematic Qur’anic interpretation as its primary approach with a Systematic Literature Review (SLR) following the PRISMA protocol. Results: The study identifies five core at-tamwīl principles derived from the Qur’an: istikhlaf (trusteeship and accountability), tanmiyah wa tazkiyah (growth and purification), tawazun wa ’adl (balance and distributive justice), tasylif wa bayyinah (clarity and evidentiary transparency), and maqashidiyyah (public welfare orientation). These principles are integrated into the "Digital At-Tamwil" model a conceptual framework that positions technologies such as blockchain, smart contracts, waqf crowdfunding, and data analytics as instruments for operationalizing Qur’anic values within digital waqf governance, rather than as replacements for Islamic ethical standards. The study further identifies ethical risks inherent to digitalization, including materialistic reductionism, digital exclusion among underserved communities, and the erosion of interpersonal bonds between donors (waqif), managers (nazhir), and beneficiaries (mustahiq). Conclusion: This research affirms that sustainable digital waqf transformation demands a strong normative grounding in Qur’anic teachings, not merely technological modernization. The Digital At-Tamwil model offers a novel contribution by bridging sacred scripture, Indonesia’s contemporary socio-economic realities, and the digital ecosystem positioning waqf as a resilient instrument of sustainable development while preserving its spiritual essence.